2012
DOI: 10.1109/tns.2012.2201499
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Dependence of CsI(Tl) Scintillation Time Constants and Intensities on Particle's Energy, Charge and Mass Through Direct Fitting of Digitized Waveforms

Abstract: The dependence of the CsI(Tl) scintillation time constants and intensities on the particle ionization profile is at the basis of the Charge and Mass identification technique for Light Charged Products in Intermediate Energy Nuclear Physics multi-detector arrays. The possibility of storing the digitized waveforms in true beam experiments allows performing further offline analyses and makes available a data set related to the interaction of different particle types in a wide energy range.We propose the direct le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 20 publications
(29 reference statements)
0
4
0
Order By: Relevance
“…Using this model, the pulse shapes for CsI(Tl) are characterized by the parameter N Hadron defined as the scintillation emission intensity of the hadron scintillation component. This single parameter pulse shape description is advantageous compared to present approaches for pulse shape characterizing techniques for CsI(Tl) where the four shape parameters (τ fast ,τ slow , N fast and N slow ) of the two component scintillation model are varied to describe the CsI(Tl) pulse shape spectrum as done in references [2] and [20]. In addition these studies have shown that low energy hadron energy deposits, which result in the largest pulse shape difference from photons, will result in fast time constants in the range of approximately 600-650 ns when fit to the two component model [20].…”
Section: Discussion Of Hadron Component Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Using this model, the pulse shapes for CsI(Tl) are characterized by the parameter N Hadron defined as the scintillation emission intensity of the hadron scintillation component. This single parameter pulse shape description is advantageous compared to present approaches for pulse shape characterizing techniques for CsI(Tl) where the four shape parameters (τ fast ,τ slow , N fast and N slow ) of the two component scintillation model are varied to describe the CsI(Tl) pulse shape spectrum as done in references [2] and [20]. In addition these studies have shown that low energy hadron energy deposits, which result in the largest pulse shape difference from photons, will result in fast time constants in the range of approximately 600-650 ns when fit to the two component model [20].…”
Section: Discussion Of Hadron Component Modelmentioning
confidence: 99%
“…This single parameter pulse shape description is advantageous compared to present approaches for pulse shape characterizing techniques for CsI(Tl) where the four shape parameters (τ fast ,τ slow , N fast and N slow ) of the two component scintillation model are varied to describe the CsI(Tl) pulse shape spectrum as done in references [2] and [20]. In addition these studies have shown that low energy hadron energy deposits, which result in the largest pulse shape difference from photons, will result in fast time constants in the range of approximately 600-650 ns when fit to the two component model [20]. This is in agreement with our model where it is expected that the τ Hadron component would dominate the scintillation emission for these pulses and thus a pulse shape description using a two component scintillation model is expected to produce a fast time constant consistent with our hadron time constant.…”
Section: Discussion Of Hadron Component Modelmentioning
confidence: 99%
“…To determine the energy of the particle where ∆E-E PID was possible, this value was calculated via the signal in the silicon stage due to the non-linear response of the CsI(Tl) crystal as well as its mass and charge signal dependence [29]. This gives an energy resolution of approximately 400 keV for a 30 MeV α-particle increasingly approximately linearly to 1000 keV for a 60 MeV α-particle.…”
Section: A Chimeramentioning
confidence: 99%
“…The same method is used with CsI(Tl) scintillators of the FARCOS array. Recently, also a digital electronics (GET) can be used, that allows the digitization of the total shape of signals [158,159].…”
Section: Chironementioning
confidence: 99%